2005
DOI: 10.1116/1.1943441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of plasma treatments on a low-k dielectric polymer surface

Abstract: The ongoing transition to lower dimension devices requires the replacement of SiO 2 by a lower-k dielectric insulator. Such materials are porous, introducing the need for sealing against penetration of gaseous and/or liquid species during subsequent processing. In this work, we investigate the effect of different plasma treatments on a porous low-k polymer film. Ion bombardment induces the formation of a dense surface layer capable of sealing the polymer. A competing etching reaction by the plasma gases determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…3 This is explained due to smaller dissociation energy for Si-C ͑ϳ447 kJ/ mol͒ compared to Si-O ͑ϳ800 kJ/ mol͒. 4 It was observed that during the carbon depletion dangling bonds occur, 5 which form new Si-O or Si-OH bonds after exposing to the atmosphere. This results in an unfavorable degradation of the dielectric properties, i.e., increasing -value.…”
Section: Introductionmentioning
confidence: 96%
“…3 This is explained due to smaller dissociation energy for Si-C ͑ϳ447 kJ/ mol͒ compared to Si-O ͑ϳ800 kJ/ mol͒. 4 It was observed that during the carbon depletion dangling bonds occur, 5 which form new Si-O or Si-OH bonds after exposing to the atmosphere. This results in an unfavorable degradation of the dielectric properties, i.e., increasing -value.…”
Section: Introductionmentioning
confidence: 96%
“…Unfortunately, dielectric degradation during certain process steps is a major concern for both LKs (major concern) and porous ULKs (much greater concern) because they are susceptible to damage during the ashing process (in particular, O 2 -based plasmas) to remove photoresist residues [152][153][154][155][156][157][158][159][160][161]. The decomposed Si-CH 3 and C-H bonds [168] can form surface silanol (Si−OH) or Si-H bonds [169] and subsequently enable bulk moisture absorption [170,171]. The decomposed Si-CH 3 and C-H bonds [168] can form surface silanol (Si−OH) or Si-H bonds [169] and subsequently enable bulk moisture absorption [170,171].…”
Section: Low-k Types and Integrating Low-k Dielectricsmentioning
confidence: 99%
“…It is reported that during plasma processes the ULK film is damaged, which is related to the carbon loss 3 . It was observed that during the carbon depletion dangling bonds occur 4 . After exposure to the atmosphere these dangling bonds can form new Si-O or Si-OH bonds.…”
Section: Introductionmentioning
confidence: 98%